Responsabilidad del estado legislador (2005)
The liability of the state because the law in Colombia; is for now; an expectation in the development law sentences; even; when the 90 constitutional article exists. In opposition to this kind of state responsibility; there are arguments like sovereignty; because it can't limit the people power to self-control, the inviolable parliamentarian vote like primitive constituent agent; even; when judicial control of law exists. It doesn't happen the same in the comparative law. French and Spain; have an admirable development about the subject. While in countries like Italy; Germany and United States such a development is shay; in England is not contemplated. The present work; it aspires to treat in short the subject in the comparative law; specially; in French and Spain law; and in the national law.